2022
DOI: 10.3390/molecules27123687
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Combining Post-Harvest Calcium Nanoparticles with a Salicylic Acid Treatment on Cucumber Tissue Breakdown via Enzyme Activity during Shelf Life

Abstract: In the present study, an experiment was carried out on the postharvest of cucumber fruit during a 14-day shelf life. The aim was to assess the impact of calcium nanoparticles (CaNPs) blended with different concentrations of salicylic acid (SA) on the shelf life of cucumbers during the seasons of 2018 and 2019. The investigation further monitored the influences of CaNPs-SA on some physical properties of cucumber, including the percentage weight loss, color, and fruit firmness. In addition, chemical properties, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The current study showed that intermixed CaNPs at 2 mM with SA delayed cell wall degrading by modulating XYL, PG, CEL, and PT, and promoting the production of antioxidant enzyme activity (CAT) (Figure 9) which decreased the MDA relative to the control (Figure 10A) over the vase life period (Youwei and Yinzhe, 2013) and increase CAT activity could aid in the scavenging of H2O2 during the vase life period (Abdelkader et al, 2022). Additionally, the presence of Ca +2 causes the middle lamella to degrade by lowering the activity of the polygalacturonase enzyme (Wehr et al, 2004).…”
Section: Discussionmentioning
confidence: 79%
“…The current study showed that intermixed CaNPs at 2 mM with SA delayed cell wall degrading by modulating XYL, PG, CEL, and PT, and promoting the production of antioxidant enzyme activity (CAT) (Figure 9) which decreased the MDA relative to the control (Figure 10A) over the vase life period (Youwei and Yinzhe, 2013) and increase CAT activity could aid in the scavenging of H2O2 during the vase life period (Abdelkader et al, 2022). Additionally, the presence of Ca +2 causes the middle lamella to degrade by lowering the activity of the polygalacturonase enzyme (Wehr et al, 2004).…”
Section: Discussionmentioning
confidence: 79%